Des troupeaux invisibles. L’imaginaire du caipira dans la grande ville - Jean Carlo Faustino (Caravelle)
According to an idea appearing in Italo Calvino’s Les villes invisibles about different ways of seeing and comprehending the city, this article proposes a reflection about the caipira paulista facing the Brazilian rural exodus of the middle of the 20th century. This study is elaborated from the analysis of the lyrics of modas de viola (a representative type of caipira song), and proposes at the same time a certain amount of sociological analysis concerned by this subject.